2023
DOI: 10.1515/ijfe-2022-0227
|View full text |Cite
|
Sign up to set email alerts
|

The properties of potato gluten-free doughs: comparative and combined effects of propylene glycol alginate and hydroxypropyl methyl cellulose or flaxseed gum

Abstract: Different methods are often used to make gluten-free (GF) bread to get better bread characteristics. To explore the effects of emulsifiers and hydrocolloids on the characteristics of GF dough, different esterification levels of propylene glycol alginate (PGA), hydroxypropyl methyl cellulose (HPMC), flaxseed gum with (FG) different molecular weight, and the binary blends of HPMC/PGA and FG/PGA were added to GF dough, made with potato starch and potato protein in a ratio of 6:4. The results showed that the potat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…As a practical example of the utilisation of FM viscosity, in one of the studies, authors added FM to potato gluten‐free bread and observed an increase in viscoelasticity. Moreover, bread fortified by FM complemented by propylene glycol alginate and hydroxyethyl cellulose exhibit improved softness (Chen et al ., 2023).…”
Section: Functional and Bioactive Propertiesmentioning
confidence: 99%
“…As a practical example of the utilisation of FM viscosity, in one of the studies, authors added FM to potato gluten‐free bread and observed an increase in viscoelasticity. Moreover, bread fortified by FM complemented by propylene glycol alginate and hydroxyethyl cellulose exhibit improved softness (Chen et al ., 2023).…”
Section: Functional and Bioactive Propertiesmentioning
confidence: 99%
“…Thus, the structural modification of polysaccharides renders it possible to modulate or endow certain functional properties by a controlled introduction of different functional groups. For instance, the introduction of hydrophobic group to hydrophilic seaweed polysaccharides provides them with amphiphilicity, thus possessing improved gelling, emulsifying, and film-forming properties (Chen, Gao et al, 2023). Introduction of hydrophilic groups (e.g., sulfate, phosphate, carboxyl groups) increases the water holding capacity of the polysaccharides.…”
Section: Functional Propertiesmentioning
confidence: 99%
“…PGA, as an emulsifier, possesses good thickening, film-forming, gelling properties, and high water solubility. It can increase the stability of yogurt and milk beverage and improve the texture of gluten-free (GF) bread (Chen, Gao et al, 2023).…”
Section: Emulsifying Propertymentioning
confidence: 99%
“…The hydroxy propyl methyl cellulose (HPMC) as nonionic modified cellulose could be used as a stabilizer and thickener. It has a high potential for creating a hydrocolloid network to replace the gluten in order to prevent the rupture of bread texture, moisture loss, and increase dough consistency, specific volume of bread, and porosity of crumb (Chen et al., 2023 ). A study has shown that the addition of 1% HPMC leads to an improvement in the internal structure of bread and an increase in the level of porosity in GF bread based on rice and buckwheat flour (Baldino et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study has shown that the addition of 1% HPMC leads to an improvement in the internal structure of bread and an increase in the level of porosity in GF bread based on rice and buckwheat flour (Baldino et al., 2018 ). In previous studies, the effects of HPMC on properties of GF bread from rice flour (Srikanlaya et al., 2022 ), different starch sources (rice flour or maize starch) (Belorio & Gómez, 2020 ), and potato starch (Chen et al., 2023 ) were studied. Pectin is another gum suggested for GF bread in which polysaccharide is derived from citrus peel or apple pomace.…”
Section: Introductionmentioning
confidence: 99%